PENGARUH KETERAMPILAN KERJA, REWARD, DAN TEAM WORK TERHADAP KINERJA KARYAWAN PADA HOME INDUSTRI TAS ANYAMAN JALI-JALI SAMBIT PONOROGO - Archika Pramita Dewi; Siti Chamidah; Titis Purwaningrum (Bussman Journal : Indonesian Journal of Business and Management, 2022)
This study aims to determine: 1). To find out whether work skills have a significant effect on employee performance in the Home industry. Jali-jali sambit woven bag ponorogo: 2). To find out whether Reward has a significant effect on the Performance of Employees in the Home Production of Jali-Jali Woven Bags in Ponorogo: 3). To find out whether Teamwork has a significant effect on the Performance of Employees in the Home Industry of Jali-Jali Sambit Woven Bags, Ponorogo: 4). To find out what are work skills , Reward, and Teamwork simultaneously have a significant effect on the performance of employees producing the Jali-Jali Sambit Home Industry of Woven Bags, Ponorogo. This research uses quantitative methods. relationships to avoid indefinite scope. The subjects used in this study as respondents were employees at the Home industry of the Jali-jali Sambit woven bag industry, Ponorogo. The results of this study indicate that work skills have a significant positive effect on employee performance, Rewards have a significant positive effect on employee performance, Teamwork has a significant positive effect on employee performance, and for work skills, rewards, teamwork have a simultaneous effect on employee performance